Digital Payment Acceptance in Higher Education: A Technology Acceptance Model Analysis from an Accounting Perspective - Fathimatus Zahro Fazda Oktavia; Atik Andhayani; Marlina Magdalena; Yusna Oktavia; Fita Setiati; Yasin Nur Rohim (Dinasti Accounting Review, 2026)
The digitalization of payment systems has driven a significant shift in financial transaction behaviour, including within higher education environments. This study aims to analyse the factors influencing the actual use of e-wallets in a university canteen using the Technology Acceptance Model (TAM) framework, while examining the implications from an accounting perspective. Unlike prior TAM studies that predominantly measure behavioural intention, this study distinctively examines Actual System Use (ASU) as the dependent variable and explicitly connects e-wallet adoption to internal control and financial documentation quality at the operational level, addressing a gap rarely investigated within vocational higher education canteens. A quantitative survey approach was employed, targeting students of Politeknik Negeri Malang who had previously transacted using e-wallets in the campus canteen. Data were analysed using multiple linear regression. Findings indicate that Perceived Usefulness and Attitude Toward Using positively and significantly affect Actual System Use, while Perceived Ease of Use shows no significant effect. Simultaneously, all three TAM variables collectively influence actual e-wallet usage. From an accounting perspective, these findings carry important implications: a higher rate of e-wallet adoption in campus canteen settings has the potential to improve the quality of automatic financial transaction recording, strengthen internal controls, and support the transparency and accountability of operational cash flows. Users' positive attitudes toward digital payment technology proved to be the dominant factor driving actual use, which indirectly contributes to more reliable audit trails compared to cash transactions. This study extends the application of TAM to the operational accounting context of higher education institutions and offers recommendations for institutional managers seeking to promote digital payment adoption as part of improved financial governance.